TOLERANCE EDUCATION ACCORDING TO THREE INDONESIAN MUFASSIRS - Marpuah, Eva; Bulqis, Dhelta Big Queen; Asnawati, Asnawati; Dewi , Elviana India Sinta (LP2M IAI Al-Khairat Pamekasan, 2025)
This research aims to analyze the thoughts on moral education, particularly tolerance, as presented by Sheikh Nawawi al-Bantani in his Tafsir al-Munir, Buya Hamka in his Tafsir al-Azhar, and Quraish Shihab in his Tafsir al-Mishbah. This research method employs a literature review approach, with the primary sources being the three tafsir books. The results of this research show that tolerance education was taught by the Prophet Muhammad SAW by strengthening the interpretation of the QS. al-Anbiya' 107. Then confirmed by QS. al-Hujurat: 13 and QS. Al-Mumtahanah: 8 regarding the diversity of humanity and the command to be fair to every group. QS. al-Baqarah: 256 as an example of a verse about the absence of coercion in religion. QS. Yunus: 41, QS. al-Kafirun: 6 and QS. Saba': 25 as an act of consideration for others in choosing their beliefs.